Well-Being Manager Competences (Journal of Universal Excellence, 2026)
Research Question (RQ): Which manager competences, considering the manner of management, are crucial for employee commitment and their well-being?Aim: To review literature and find the competences that a well-being manager requires, and study differences between the USA, Europe and Slovenia.Method: We have reviewed literature about well-being manager competences in the USA, Europe and Slovenia. We have classified the literature about the working population according to the IGLO principle (Individual level, Group level, Level of a Leader and Organisational level). We have compared research results within the research frames of the EU, the USA and Slovenia, and evaluated them critically.Results: What all the countries/fields have in common is that organisations do not do business successfully without a successful leader. A successful leader should have a wide variety of competences. They should not only be successful in the conduct of business, organise work, achieve corporative goals and produce high profit, but mostly be good at work and have good relationship with their employees. A good manager/leader should be, first and foremost, a person. A leader recognises the importance of leadership and the need for continuous development of good leadership competences in a fast-changing world. To create a work climate at the will of the majority, they need to obtain feedback from employees at all times.Organisation: A competent manager is crucial for a long-term success of the organisation. If a manager fails to invest in relationship with the employees and does not establish the necessary connections with them, it is difficult or even impossible to achieve the goals of the organisation. There are several levels of manager competences: social skills, personal maturity, interest for education and continuous development at the personal and the professional level. By using inspirational observations, leaders can create a feeling of sense, whereas the pressure tactics reduces employees’ feeling of sense and commitment.Society: A leader with developed manager competences has a positive influence on employees, increases their commitment and productivity, reduces their fluctuation, enables higher productivity and with that profitability of the organisation. A successful organisation can have a positive effect on the local community, the wider society and the natural environment.Originality: In a globalising world with focus on scientific research, this article points out the orientation of manager competences towards human values that are crucial for achieving goals. Originality of the article can be seen in the comparison of manager competences in the USA, Europe and Slovenia, which has shown similarities and differences in the approach to organisation management.Limitations/Further research: The article is limited by a small number of articles gathered for comparison. A larger number of articles would have led to more relevant conclusions. Evaluation of employee commitment and relevance of manager competences is in most cases based on subjective consideration. Emphasis should be placed on individual competences and their effect measured in parallel.
Keywords: well-being managers; well-being manager competences; employee commitment; leadership; leader; employee satisfaction; manager competences; stress